Effect of particle size, fraction and carbide banding on deformation and damage behavior of ferrite–cementite steel under tensile/shear loads. (7th December 2016) - Zhuang, Xincun; Ma, Siming; Zhao, Zhen
Abstract: Deformation and damage behavior of ferrite–cementite steel was investigated using microstructure-based representative volume element (RVE) methodology. A series of automatically generated 2D RVEs with ferrite matrix and globular cementite particles were generated as representative of various microstructures. The geometrically necessary dislocation (GND) accumulation at the ferrite–cementite interphase was also studied by introducing an intermediate layer around the cementite particles. Damage mechanisms such as ductile fracture in ferrite matrix, brittle fracture in cementite, and decohesion at ferrite–cementite interphase were considered to study the fracture modes. The relationships between interface strength and particle size were estimated according to the modified Argon criterion and showed satisfactory agreement with related works. The influences of microstructural features, such as particle size, particle fraction and carbide banding, on deformation and damage evolution were investigated under tensile and shear loads. Simulation results indicated that small particle size and particle fraction could postpone the initial decohesion under both tensile and shear loads, while carbide banding can lead to early fracture due to local stress concentration, which has potential to cause the loss of ductility and premature failure. These adverse effects become more severe when more cementite particles remain in the band or the gather density of the cementite particles in the band becomes higher.